Over-the-counter medication use among Mexican immigrants in Southern Arizona: a cross-sectional study - Ochoa Mora, Estefania; Maldonado, Adriana; Flores, Melissa; Rodríguez, Mariella; Martínez, Daniel E.; Crocker, Rebecca; Garcia, David O. (Frontiers in Public Health, 2025)
IntroductionOver-the-counter (OTC) medication use is high among Mexican immigrants before migrating to the U.S. However, changes in OTC medication use during migration process remain unclear. This study describes OTC medication use patterns among Mexican immigrants in Southern Arizona, explores changes caused during the migration process, and examines the influence of sociodemographic factors on OTC medication use.MethodsA cross-sectional study was conducted using a purposive community-based sample (n = 300) of Mexican immigrant adults. Poisson regression model was utilized to assess the relationship between perceived discrimination, importance of health care use, pre-existing chronic health conditions, years living in the U.S. and the number of OTC medications used in the U.S. while adjusting for demographics and number of OTC medications used in Mexico.ResultsAcetaminophen, NSAID, and supplement use increased post-migration. The number of OTC medications used in Mexico was associated with OTC medication use in the U.S. (RR = 1.35, 95% CI: 1.26, 1.45). Men in the U.S. had a 24% lower rate of OTC medication use compared to women (RR = 0.76, 95% CI: 0.59, 0.97). Length of stay in the U.S. was significantly associated with OTC medication use (95% CI: 0.00, 0.38; p = 0.002). Divorced/separated individuals had a 29% lower rate of OTC use compared to married individuals (RR = 0.71, 95% CI: 0.53, 0.96).DiscussionThis study is among the first to examine OTC medication use patterns among Mexican immigrants in Southern Arizona. Further research is needed to understand the factors driving these changes and their impact on health outcomes.